Nanocomposite Biosensors for Cancer Biomarker Detection: From Sensing Mechanisms to Prognostic Applications - Saraç, Begüm; Adıgüzel, Burhan; Yücer, Şeydanur; Karabağ, Dilara Gülsüm Özdemir; Şahin, Berfin Gürbüz; Çiftçi, Fatih (Elsevier, 2026)
Nanocomposite biosensors have emerged as promising tools in the field of cancer detection and prognosis due to their enhanced sensitivity, selectivity, and rapid response times. These biosensors integrate nanomaterials such as graphene, carbon nanotubes, and metal nanoparticles within polymer matrices, resulting in hybrid materials that exhibit superior electrical, mechanical, and chemical properties. The design and working principles of nanocomposite biosensors rely on the synergistic interactions between the nanomaterials and biological recognition elements, such as antibodies, DNA probes, or aptamers, enabling highly specific detection of cancer biomarkers at low concentrations. In cancer diagnosis and prognosis, nanocomposite biosensors have demonstrated considerable potential by facilitating early and accurate detection of tumor-associated markers, which is crucial for improving patient outcomes. These biosensors are applied in various formats including electrochemical, optical, and piezoelectric platforms, each offering distinct advantages for monitoring cancer progression and response to treatment. The incorporation of nanocomposites enhances signal transduction and stability, thereby improving the reliability and reproducibility of measurements. Recent studies have highlighted their use in detecting biomarkers such as circulating tumor DNA, proteins, and microRNAs, which are pivotal in understanding cancer aggressiveness and patient prognosis. Looking forward, the development of nanocomposite biosensors is expected to advance further through integration with microfluidic systems and wearable devices, enabling real-time, point-of-care cancer monitoring. Challenges such as large-scale production, biocompatibility, and long-term stability remain, but ongoing research aims to address these barriers. This review uniquely provides a comparative evaluation of nanocomposite biosensors based on sensing mechanisms, analytical performance, and clinical applicability, offering a new classification framework for next-generation cancer biomarker detection technologies. Overall, nanocomposite biosensors represent a transformative approach in oncology, offering precise, non-invasive, and cost-effective solutions for cancer detection and prognosis, ultimately contributing to personalized medicine and improved clinical outcomes.
Keywords: Nanocomposite Biosensors; Cancer Detection; Biomarkers; Electrochemical Sensing; Point-of-Care Diagnostics; Prognosis